PENINGKATAN PENDAPATAN MASYARAKAT PEDESAAN DALAM HUBUNGANNYA DENGAN DISTRIBUSI ANTAR RUMAH TANGGA - A. ROZANY NURMANAF (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2005)
The purpose of this study is to show interrelation between the level ofdevelopment successful and income distribution inequality among households.By using Patanas data 1999 especially the information that covered householdincome aspect, this study identify the shape of relationship between twoparameters these are the skewness of household income distribution thatis measured by Gini Index value and level of income that is calculatedin income per head. Based on the village analysis unit, the discussionfocused on the shape of the two in order to examine Kuznets hypothesisthat represent by U-shape pattern. The analysis of study verified thatthe relationship support the hypothesis. It means, increasing in householdincome followed by increasing in household income distribution skewnessespecially in the beginning of development phase; but this tendency changein opposite way in next development phase. While, the level of incomedistribution skewness have positive correlation with three income factors,these are distribution of agricultural income, distribution of householdmember education level and distribution of agricultural land holding.Besides, the distribution of agricultural income is affected by the distributionof agricultural land holding, especially in the area where agriculturalsector has a higher contribution on the economy of society.